Pengaruh Model Pembelajaran Project Based Learning Berbasis E-Magazine Terhadap Kemampuan Berpikir Historis Siswa di SMA Negeri 9 Pandeglang - Dini Melinda Ayu; Eko Ribawati; Rikza Fauzan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to determine the effect of the e-magazine-based project based learning model on historical thinking skills in History learning for class XI at SMA Negeri 9 Pandeglang. The research method used in this study is a quasi-experimental with. Data collection was carried out through a purposive sample technique with class XI B consisting of 34 students as the experimental class using the PjBL model and class XI C consisting of 34 students as the control class using the discovery learning model. The results of the study are as follows; (1) there is an effect of the e-magazine-based project based learning model on students' historical thinking skills, hypothesis testing through a two-way t-test using the polled variant diporel formula, t count = 5,151 ≥ t table = 1,996 with α = 0.05, (2) the historical thinking skills of students who use the project based learning model are higher than students who use the discovery learning model. The average post-test score of the experimental class (77,4) and the control class (68,9) showed that the control class had an average difference of (8,5) higher than the control class. Indicators of chronological thinking skills, skills in identifying continuity and change, indicators of recording data/information/historical sources, skills in identifying continuity and change, and skills in designing and reporting historical research results experienced changes and increases seen from before and after the treatment of the project based learning model in the form of cause and effect ideas on learning materials, analysis at the discussion stage, and compiling and reporting the results of reports according to the selected topic. Based on the results of the t-test analysis, the t-count value = 5,151 and t-table = 1,996 were obtained with a significance level of 0,05, so it was concluded that there was an influence of the use of the e-magazine-based project based learning model on students' historical thinking skills at SMA Negeri 9 Pandeglang.